2017
DOI: 10.1016/j.nicl.2017.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative susceptibility mapping to evaluate the early stage of Alzheimer's disease

Abstract: The objective of this study was to evaluate susceptibility changes caused by iron accumulation in cognitive normal (CN) elderly, those with amnestic mild cognitive impairment (aMCI), and those with early state AD, and to compare the findings with gray matter volume (GMV) changes caused by neuronal loss. The participants included 19 elderly CN, 19 aMCI, and 19 AD subjects. The voxel-based quantitative susceptibility map (QSM) and GMV in the brain were calculated and the differences of those insides were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
90
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 40 publications
9
90
0
1
Order By: Relevance
“…Quantitative susceptibility mapping and R2* have been used to quantify the amount of iron present in the brains of healthy individuals and in patients with Parkinson disease, Alzheimer disease, and multiple sclerosis (13)(14)(15)(16)(17)21). Our results are consistent with these studies, two of which were postmortem examinations (14,17), and it shows a reliable correlation between both susceptibility and R2* and iron-rich regions in the brain.…”
Section: Discussionsupporting
confidence: 88%
“…Quantitative susceptibility mapping and R2* have been used to quantify the amount of iron present in the brains of healthy individuals and in patients with Parkinson disease, Alzheimer disease, and multiple sclerosis (13)(14)(15)(16)(17)21). Our results are consistent with these studies, two of which were postmortem examinations (14,17), and it shows a reliable correlation between both susceptibility and R2* and iron-rich regions in the brain.…”
Section: Discussionsupporting
confidence: 88%
“…As the magnetic properties of tissue can be affected by both the cellular composition and arrangement of fiber bundles (39,40), combining DTI with QSM to detect axonal damage and demyelination can potentially lead to new insights and more robust identification of white matter pathology post-injury. To date, QSM has provided additional insight into white matter pathologies in multiple sclerosis and Alzheimer's disease (36,(41)(42)(43). Yet there has been a lag in the acceptance of the method for the analysis of traumatic axonal injury.…”
Section: Introductionmentioning
confidence: 99%
“…Many clinical studies of QSM analysis have reported estimates of subtle susceptibility changes in the brain that occur with neuroinflammatory and neurodegenerative diseases . For example, regional iron deposition associated with amyloid‐β aggregation has been observed in the cortical and deep gray matter (GM) and white matter (WM) in Alzheimer's disease (AD) . Similarly, the susceptibility value in the substantia nigra (SN) has been found to be increased in Parkinson's disease (PD) progression and has been correlated with symptoms related to dopaminergic neurodegeneration .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the evaluation of brain atrophy and iron aggregation may be valuable for the early diagnosis and staging of these diseases. At the present time, several studies have attempted anatomical standardization of the susceptibility map in order to perform statistical voxel‐based analysis via whole brain or atlas‐based analyses . Kim et al have reported that the susceptibility value was better able to differentiate AD and mild cognitive impairment by using dual voxel‐based and region of interest (ROI)‐based analyses, and they found that this can aid in the early diagnosis of AD .…”
Section: Introductionmentioning
confidence: 99%